Augmented Reality as Anti-Corruption Education Media in Islamic Religious Education Teaching - Nasikhin Nasikhin; Ikhrom Ikhrom; Raharjo Raharjo; Nasikhin Jalis (DAYAH: Journal of Islamic Education, 2023)
This study aims to develop augmented reality as an anti-corruption educational media in the teaching of Islamic religious education. Data processing using research and development methods ADDIE model. Validity tests and measurement of N-Gain scores were used to see the effectiveness of the product. Three junior high schools with different environmental characteristics participated in this study. The findings of this study indicate that; first, the development of augmented reality for the realm of anti-corruption education can be adapted to the Basic Competencies of Islamic Religious Education subjects on the themes of honesty, trustworthiness, and istiqomah for class VII Semester 2. Second, there is an increase in knowledge of the value of anti-corruption education for students of SMP N 02 Bawang by 79.5%, 79% of students of SMP N 01 Subah, and 80.44% of SMP N 01 Batang students. On the N-gain scale, the three achievements are considered effective. In fact, the environmental characteristics of the three schools are different. SMP N 02 Bawang is located in a mountainous area, SMP N 01 Subah is located in the northern coastal area, while SMP N 01 Batang is located in an urban area. This raises the meaning that augmented reality has a good impact on increasing anti-corruption knowledge in educational teaching in institutions with different environmental characteristics. This study recommends that these findings can be used as a basis for consideration in determining policies and implementing anti-corruption education in augmented reality technology-based junior high schools.